2015
DOI: 10.1124/jpet.115.222802
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride and GMQ Allosteric Modulation of the GABA-A ρ1 Receptor: Influences of the Intersubunit Site

Abstract: Amiloride, a diuretic used in the treatment of hypertension and congestive heart failure, and 2-guanidine-4-methylquinazoline (GMQ) are guanidine compounds that modulate acid-sensing ion channels. Both compounds have demonstrated affinity for a variety of membrane proteins, including members of the Cysloop family of ligand-gated ion channels, such as the heteromeric GABA-A abg receptors. The actions of these guanidine compounds on the homomeric GABA-A r1 receptor remains unclear, especially in light of how man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The positive allosteric modulatory activity of HMA in the mutant receptor was unexpected, as the same mutation abolished amiloride activity in a previous study. 14 We speculate that the isoleucine to asparagine mutation facilitated HMA interaction, possibly through accommodating the HMA azapine ring within the site. Additionally, the I15'N mutation may alter the activity of the GABA-A r1 receptor and modify the amiloride/amiloride-derivative site, where the site is a distinct site separate from the channel's second transmembrane domain 15' site.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The positive allosteric modulatory activity of HMA in the mutant receptor was unexpected, as the same mutation abolished amiloride activity in a previous study. 14 We speculate that the isoleucine to asparagine mutation facilitated HMA interaction, possibly through accommodating the HMA azapine ring within the site. Additionally, the I15'N mutation may alter the activity of the GABA-A r1 receptor and modify the amiloride/amiloride-derivative site, where the site is a distinct site separate from the channel's second transmembrane domain 15' site.…”
Section: Discussionmentioning
confidence: 86%
“…Previously, we reported that the GABA-A r1 (I15'N) mutant receptor was insensitive to amiloride. 14 This site within the interface of 2 neighboring GABA-A r1 receptor subunits is an appealing candidate for an amiloride derivative site of action. To further probe this site, we assessed the mutant receptor for HMA, phenamil, and benzamil activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations